Paleoplacer Potential in the Mid-Proterozoic of the Northern Territory-A Study of the Westmoreland Conglomerate - Hallenstein CP; Wygralk A (The Australasian Institute of Mining and Metallurgy, 1984)
On a world scale, many Mid-Proterozoic fluvial sediments are prospective for low grade, large-tonnage gold deposits. A significant area of the Northern Territory is covered by such Mid-Proterozoic sediments, the gold potential of which has been barely tested. The geological knowledge of these sediments is summarised. The Westmoreland Conglomerate, the basal Mid-Proterozoic formation of the McArthur Basin, has been subjected to detailed sedimentological studies in order to determine the paleoenvironments and to assess the possibility of paleoplacer occurrences. The results indicate that the sandstones and conglomerates of the formation were deposited by braided rivers and debris flows as an alluvial fan which originated in source areas to the north east. The formation contains several upward-fining cycles of sedimentation, which are related to repeated periods of uplift in the source areas. The formation of placer-type gold occurrences is possible in such depositional environments. Very limited heavy mineral sampling has indicated a cassiterite- wolframite-gold suite in the sediments of the Westmoreland Conglomerate. Disconformities at the base of sedimentation cycles are deemed to be the most likely sites for large-tonnage paleoplacer concentrations.